The Role Of Traditional Villages In Managing Human Resources Management Based On The Awig-Awig Of Bebetin Village - I Gede Dimas Wira Prasetya (CV Putra Publisher, 2023)
This research aims to determine the role of Pat Likur Village in the Human Resources Management management process and to determine the role of customs, traditions, and awig-awig in the Human Resources Management management process in Pakraman Bebetin Village. This research method uses qualitative or non-positivist with an interpretive paradigm. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, and data presentation. The results of this research show that the role of Pat Likur Village greatly influences the management of Human Resources Management in Pakraman Bebetin Village. Pat Likur Village is a custom that has been passed down from generation to generation which sacredly and specifically has a very dominating role in the management of the Traditional Village, especially the management of its human resources. Awig-awig which is formed through data through deliberation and consensus is carried out with full responsibility by traditional village communities and provides management of their human resources in a more effective and efficient direction. The human resources of the Bebetin Traditional Village greatly influence the management of the village which is regulated in the form of awig-awig.